The Effectiveness of Android-Based Tajwid Learning Media on Qur'an Living Literature Activities in Increasing Student Tajwid Learning Outcomes - Cela Petty Susanti; Bakhruddin Fannani; M Samsul Ulum (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
ABSTRACKThis study aims to: (1) find out the procedures for developing Android-based Tajweed learning media in improving student learning outcomes at the University of Muhammadiyah Malang, and (2) determine the effectiveness of Android-based Tajweed learning media in improving student learning outcomes at the University of Muhammadiyah Malang. To achieve the above objectives, researchers use a type of research and development model of qualitative descriptive and quantitative descriptive approaches. Data collection techniques used were observation, interviews, questionnaires and documentation. The product design used is the Borg and Gall model which consists of 7 stages, namely (1) needs analysis, (2) product design, (3) development process, (4) expert validation, (5) product revision, (6) field trials, (7) final products. Results from Design Experts reach 100% (Very Valid). Researchers conducted trials through two stages: limited trials reaching a percentage of 98.86% (Very Valid) and field trials reaching a percentage of 93.5% (Very Valid). This study shows that an increase in student learning outcomes at the University of Muhammadiyah Malang. From the control group and the experimental group the t value in the control group was 3.056 and the t value in the experimental group was 4.879. All Ho was rejected because the value of t> t table = 0.2785 with a ratio of 0.736 was more effective using the Android-based Tajweed learning media that researchers developed.